Physico-mechanical and film-forming properties of carboxymethyl corn starch butyrate - Kittipongpatana O. (2017)
© 2016 The Authors. Published by Innovare Academic Sciences Pvt Ltd. Objective: This study aims to prepare a new hydrophobic, water-soluble modified corn starch via sequential butyrylation and carboxymethylation and to evaluate its physico-mechanical and film-forming properties. Methods: Butyrylation of corn starch (CS) was carried out in an aqueous suspension using 25%w/w butyric anhydride to yield corn starch butyrate (CSB). CSB was further reacted with chloroacetic acid to carboxymethyl corn starch butyrate (CMCSB). Following the determination of the degrees of carboxymethyl substitution (DS-Cm) and butyrylation (DS-Bu), CMCSB was subjected to analyses by scanning electron microscopic (SEM), X-ray diffraction (XRD), solubility, viscosity, free swelling capacity (FSC), moisture sorption, film formation and water vapor transmission rate (WVTR). Results: DS-Cm of CMCSB was 0.24, while DS-Bu was 0.09. SEM images revealed significant granules fusion and surface roughness. XRD showed a decrease in the degree of crystallinity. CMCSB was soluble in water, with a three times lower viscosity than that of carboxymethyl corn starch (CMCS). Initial FSC of CMCSB was slightly lower than that of CMCS, but gradually increased to a higher FSC after 30 min. A significant drop of moisture sorption from 20% in CMCS to 11% in CMCSB was observed at 93% relative humidity. CMCSB formed an intact film with slightly better flexibility than that of CMCS. WVTR of CMCSB was decreased by a maximum of 4.9% compared to CS, and 10.2% compared to CMCS. Conclusion: The introduction of the butyrate group increased the hydrophobicity of the modified starch, altered some of the physico-mechanical properties, and enhanced the barrier property of the modified starch film.